An Exploration of the Cultural Adaptation Process during an International Experience inFrance - Nathan W. Conner; T. Grady Roberts; James Sterns (Journal of International Agricultural and Extension Education, 2016)
The purpose of this study was to explore how a group ofstudents experienced cultural adaptation during a short-term study abroad program in Paris, France. The intrinsic case studywas usedand data collection methods included pre-experiencequestions, reflective journaling, post-experience questions,and participant observation. The grounded theory analysis methodwas used to identify the following eightstages of cultural adaptation:a) Initial Feelings, b) Cultural Uncertainty, c) Cultural Barriers, d) Cultural Negativity, e) Group Dynamics, f) Academic and Career Growth, g) Feelings throughout the Program, and h) Cultural Growth. Findings indicated that participants experienced cultural adaptation in anon-linear fashionand study abroad facilitators should incorporate and encourage cultural learning.
Keywords: Study Abroad; Cultural Adaptation; Experiential Learning; Globalization